Pengaruh Variabel Independen Terhadap Capital Adequacy Ratio Industry Perbankan - Cassie Bun, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study is to find out and analyze the influence of non performing loans, size, credit risk, net interest margin, and deposit asset ratio to capital adequacy ratio. The research method used was purposive sampling with a total sample of 36banking companies listed on the Indonesia Stock Exchange (IDX). This research was conducted using years of observation, namely 2015-2017. The type of data used is secondary data. Data is obtained from financial statements taken from www.idx.com. Data analysis method used is classical assumption analysis, descriptive statistical test, f test, t test and test coefficient of determination. Testing the hypothesis in this study uses the t test. The results of the study show that the size, net interest margin anddeposit asset ratio do not have a significant effect on capital adequacy ratio, while non performing loanshave a negative effect on capital adequacy ratio. The last results show that net interest margin have a positive effect on capital adequacy ratio